2011
DOI: 10.1055/s-0030-1269532
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration associated protein ALR exhibits anti-metastatic potential in hepatocellular carcinoma

Abstract: Augmenter of liver regeneration (ALR), which is critically important in liver regeneration and hepatocyte proliferation, is highly expressed in cirrhotic livers and hepatocellular carcinomas (HCC). In the current study, the functional role of ALR in hepatocancerogenesis was analyzed in more detail. HepG2 cells, in which the cytosolic 15 kDa ALR isoform was reexpressed stably, (HepG2-ALR) were used in migration and invasion assays using modified Boyden chambers. Epithelial-mesenchymal transition (EMT) markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…In HCC tissue, ALR typically demonstrates cytoplasmic localization with a granular quality on immunostaining (20). Dayoub and colleagues, however, observe the short ALR isoform of 15 kDa to be expressed at lower levels in HCC overall, compared to normal liver tissue (11). Furthermore, this study found ALR expression to be inversely correlated with tumor grade and histologic angioinvasion.…”
Section: Hepatocellular Carcinomacontrasting
confidence: 53%
See 2 more Smart Citations
“…In HCC tissue, ALR typically demonstrates cytoplasmic localization with a granular quality on immunostaining (20). Dayoub and colleagues, however, observe the short ALR isoform of 15 kDa to be expressed at lower levels in HCC overall, compared to normal liver tissue (11). Furthermore, this study found ALR expression to be inversely correlated with tumor grade and histologic angioinvasion.…”
Section: Hepatocellular Carcinomacontrasting
confidence: 53%
“…Full-text review eliminated one article that was an editorial and did not contain original data. Ultimately, 12 articles were included in the present review (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Study characteristics are summarized in Table I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analysis of the testes at defined time points after birth, the testes were collected and single-cell cells [11]. The full-length 23kDa mammalian ALR is predominant and localized in the mitochondrial intermembrane space, and is an important component of a disulfide-redox relay system [12].…”
Section: Germ Cell Preparation and Flow Cytometrymentioning
confidence: 99%
“…In practice, administration of an HSS-bearing plasmid by hydrodynamic tail vein injection protects mice from hepatic failure, implying its potential role in clinical application. It has been demonstrated that alterations in HSS gene expression could be observed in relation to pathological states, such as acute liver failure (Li et al, 2011), liver cirrhosis (Gribilas et al, 2009), and hepatocellular carcinoma (Thasler et al, 2005;Dayoub et al, 2011). HSS seems to have additional clinical implications because exogenous HSS administration to rats with thioacetamide-induced liver fibrosis/cirrhosis is able to significantly decrease fibrosis and suppress the onset of cirrhosis (Gribilas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%